The Influence of the Problem Based Learning Model assisted by Mind Mapping on the Cognitive Learning Outcomes of High School Students on Respiratory System Material - Valentina Yentina Simatupang, Valentina Yentina Simatupang; Nugrahaningsih WH (Journal of Biology Education, 2024)
Respiration material is material that is difficult to understand because the material coverage is broad. Learning cannot yet require students to be active and train students to discover concepts independently. The aim of this research is to analyze the influence of the Problem Based Learning model assisted by Mind Mapping on the cognitive learning outcomes of high school students in the respiratory system material, analyze student responses, and analyze teacher responses to the application of the Problem Based Learning model assisted by Mind Mapping. This research design is quasi-experimental with a nonequivalent control group design. The population in this study was class XI students at SMAN 12 Semarang and the sampling technique was purposive sampling. The sample in this study was students in class XI F-2 (experimental class) and XI F-4 (control class) with 34 students in each class. Student cognitive learning outcomes were measured using test instruments in the form of pretest and posttest questions in multiple choice form, then analyzed using the classical learning mastery test, t-test and N-Gain test. Teacher responses were measured using interview instruments and student responses using a questionnaire sheet. The results of the classical learning completeness test in the experimental class were 100% with the number of students who completed it, while in the control class it was 67.6% with the number of students who completed it as many as 23 people. The results of the t-test analysis on the pretest showed that there were no significant differences between the experimental and control classes, while the t-test analysis on the posttest showed that there were significant differences between the experimental and control classes. The results of the N-Gain test showed that the increase in cognitive learning outcomes in the experimental class was in the high category at 0.77, while the control class was in the medium category at 0.38. The teacher's response to the Problem Based Learning model assisted by Mind Mapping was very good because it was effective in achieving learning outcomes and objectives, student responses showed a positive or good response to the learning carried out. The conclusion of this research is that there is an influence of the Problem Based Learning model assisted by Mind Mapping in improving the cognitive learning outcomes of class XI students on the respiratory system material and getting a positive response from teachers and students.